Development of innovative portable washing machine / Anna Jasmine Hariulnizam and Miqdad Khairulmaini - Hariulnizam, Anna Jasmine; Khairulmaini, Miqdad (School of Mechanical Engineering, 2023)
The project focuses on developing a portable washing machine for college students who face challenges in doing their laundry by hand. The absence of a washing machine for students in college can lead to dripping clothes and physical exhaustion, and thus, a portable washing machine that can be operated in their own time is needed. The primary objective of this project is to design a cost-effective prototype that is convenient and mobile. The manufacturing processes involved in creating this prototype, such as welding and sheet metal bending, are explored in this report. The result of this project will be a better quality of life for college students and potentially others who find the prototype useful. The significance of this project lies in its ability to provide a solution for college students who are unable to afford or have access to washing machines. The portable washing machine will improve the lives of college students by saving time and energy while providing convenience and mobility. The prototype will be named ALENTA, and its development will set a new standard for portable washing machines in the market.